2012
DOI: 10.4161/psb.7.1.18637
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatments, conditioned medium and co-culture increase the incidence of somatic embryogenesis of different Cichorium species

Abstract: Somatic embryogenesis (SE) in Cichorium involves dedifferentiation and redifferentiation of single cells and can be induced by specific in vitro culture conditions. We have tested the effect of various treatments on the incidence of SE (ISE) of an interspecific embryogenic hybrid (C. endivia x C. intybus) and of different commercial chicories (C. endivia and C. intybus) that are typically recalcitrant to SE in standard culture conditions. We found that the ISE of the hybrid is significantly increased by pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 78 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…Several other researchers demonstrated auxins specifically 2,4-D’s efficacy (as most significant and strong PGR) in initiating somatic embryos in different plant species (Zhang et al 2007 ; Gulzar et al 2019 ). Since Daucus carrota, the incidence of somatic embryogenesis has been reported widely and histological and SEM evidence has been presented in many plant species (Couillerot et al 2012 ; Mujib et al 2013 ). The induced somatic embryos of Tylophora were later germinated and produced plants in BAP and GA 3 added medium.…”
Section: Discussionmentioning
confidence: 99%
“…Several other researchers demonstrated auxins specifically 2,4-D’s efficacy (as most significant and strong PGR) in initiating somatic embryos in different plant species (Zhang et al 2007 ; Gulzar et al 2019 ). Since Daucus carrota, the incidence of somatic embryogenesis has been reported widely and histological and SEM evidence has been presented in many plant species (Couillerot et al 2012 ; Mujib et al 2013 ). The induced somatic embryos of Tylophora were later germinated and produced plants in BAP and GA 3 added medium.…”
Section: Discussionmentioning
confidence: 99%
“…Glycerol is a polyol that can be produced either through glycolysis or as a product of photosynthetic carbon fixation (Gerber et al ., ). The function(s) of glycerol in plant biology are still not totally clear, but previous studies have suggested roles for it in root development (Hu et al ., ), somatic embryogenesis (Bellettre et al ., ; Wu et al ., ; Couillerot et al ., ), abiotic stress response (Eastmond, ; Chen and Jiang, ) and the plant immune system (Chanda et al ., ; Li et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Proline accumulation diminished reactive oxygen species (ROS) levels in wheat by increasing peroxidase and catalase levels, and thus protected it from salinity stress (Manjili et al, 2012). The addition of amino sugars and proline (17.36 mM) together to in vitro medium increased the incidence of somatic embryogenesis by 4-to 5-fold in Cichorium (Couillerot et al, 2012). In a comparative study on rice, proline supplementation (24.32 mM) to in vitro media increased scutellar callus fresh and dry weights more than any other supplemented amino acids did (Pazuki et al, 2015).…”
mentioning
confidence: 99%